Analisis Yuridis Pencegahan Dan Penanganan Kekerasan Seksual di Lingkungan Universitas Prima Indonesia (Pasca Pemberlakuan Permendikbud Nomor 30 Tahun 2021) - Stephanie, Stephanie; Surbakti, Anton Diary Steward (UNES Law Review, 2024)
This study aims to analyze the effectiveness of policies for the prevention and handling of sexual violence at Prima Indonesia University. Prevention measures are implemented to avoid, reduce the risk of, and/or mitigate the consequences of sexual violence. Sexual violence is an act of imbalance that results in psychological or physical suffering. Sexual violence within university environments has become a serious and widely discussed issue. This study employs a normative research method. The findings indicate that the prevention efforts carried out by Prima Indonesia University are considered quite effective, as there have been no reported cases of sexual violence at the university to date. However, the dissemination of information regarding prevention and handling policies is still lacking, necessitating increased socialization and education on sexual violence.